IPO Underpiricing, Accounting Conservatism, and Herd Behavior - Wibowo, Buddi (Jurnal ASET (Akuntansi Riset), 2021)
IPO underpricing is an example of anomalous behavior in capital market. Stock price in primary market tends to very low and then increases signifinactly in adjacent secondary market.Â  If we believe that stock issuer would not leave the money on the table, so this anomaly must come from investorsâ€™ irrational behavior or lack of information in secondary market. Accounting conservatism plays an important role in reporting a fair financial condition which is basic information for investor to set fair stock price. Accounting conservatism gives a strong signal to market participant that the company always exposes real dan honest its financial performance so gives no room for speculation of its stock price in the market. However, mispricing in secondary market is not only affected by speculative behavior but also herding behavior where retail uninformed investors tend to follow market leader and create a speculative stock price wave. This study show that accounting conservatism and herding behavior are crucial factor in understanding contradicting behavior in primary and secondary market in Indonesia Stock Exchanges